Carbapenem-Resistant Gram-Negative Bacilli Causing Ventilator Associated Pneumonia: Study of MASTDISCS Combi Carba Plus for Detection of Carbapenemase Producing Enterobacterales - Hegazy EE; Bahey MG; Abo Hagar AM; Elkholy AA; Mohamed EA (Infection and Drug Resistance, 2022)
Eman E Hegazy,1 Marwa Gamal Bahey,1 Alaa Mohammed Abo Hagar,2 Amira Abdelgalil Elkholy,3 Esraa A Mohamed1 1Department of Medical Microbiology and Immunology, Faculty of Medicine, Tanta University, Tanta, Egypt; 2Department of Anesthesiology, Surgical Intensive Care and Pain Medicine, Faculty of Medicine, Tanta University, Tanta, Egypt; 3Department of Chest Diseases, Faculty of Medicine, Tanta University, Tanta, EgyptCorrespondence: Eman E Hegazy, Tel +20 10 99008274, Email dr_emanhegazy2010@yahoo.comBackground: Ventilator-associated pneumonia (VAP) caused by carbapenem-resistant gram-negative bacteria has been proven to be an escalating public health challenge in Egypt owing to its high mortality rate and raised health care costs.Purpose: Detection of carbapenem-resistant gram-negative bacilli among VAP patients, genotypic identification of carbapenemase genes in the isolated strains with evaluation of their impact on patient outcome and detection of carbapenemase-producing enterobacterales by MASTDISCS combi Carba plus disc system.Methods: Broncho-alveolar lavage fluid (BALF) and endotracheal aspirate were collected aseptically from clinically suspected VAP patients. Pathogen identification and antibiotic sensitivity testing were done. Carbapenemase-encoding genes (blaKPC, blaNDM, and blaOXA-48) were tested by PCR in all carbapenem-resistant gram-negative isolates. Performance of MASTDISCS combi Carba plus in isolated Enterobacterales was assessed in relation to the PCR results.Results: Eighty-three carbapenem-resistant gram-negative isolates were detected. The most frequent pathogens were Klebsiella pneumoniae, Acinetobacter baumannii and Pseudomonas aeruginosa representing 34.9%, 20.5% and 18.1%, respectively. blaKPC was the predominant gene. Patients with persistent mechanical ventilation less than 15 days and Pseudomonas aeruginosa infection were significantly associated with a higher death rate. MAST-Carba plus had the highest sensitivity, specificity, positive and negative predictive values for detecting OXA-48 carbapenemases representing 81.8%, 92.5%, 75% and 94.9%, respectively.Conclusion: Worse outcome in VAP patients was associated with carbapenem-resistant gram-negative bacilli. MASTDISCS combi Carba plus is an efficient simple method for identification of different carbapenemases among enterobacterales.Keywords: Mast DISCS, carbapenemase, enterobacterales, ventilator-associated pneumonia, VAP